The yellow birds [large type] : a novel - Powers, Kevin (Thorndike Press, 2012)
In the midst of a bloody battle in the Iraq War, two soldiers, bound together since basic training, do everything to protect each other from both outside enemies and the internal struggles that come from constant danger.